Antimicrobial stewardship of antiseptics that are pertinent to wounds: the need for a united approach. Issue 1 (25th March 2021) - Maillard, Jean-Yves; Kampf, Günter; Cooper, Rose
Abstract: Long before the nature of infection was recognized, or the significance of biofilms in delayed healing was understood, antimicrobial agents were being used in wound care. In the last 70 years, antibiotics have provided an effective means to control wound infection, but the continued emergence of antibiotic-resistant strains and the documented antibiotic tolerance of biofilms has reduced their effectiveness. A range of wound dressings containing an antimicrobial (antibiotic or non-antibiotic compound) has been developed. Whereas standardized methods for determining the efficacy of non-antibiotic antimicrobials in bacterial suspension tests were developed in the early twentieth century, standardized ways of evaluating the efficacy of antimicrobial dressings against microbial suspensions and biofilms are not available. Resistance to non-antibiotic antimicrobials and cross-resistance with antibiotics has been reported, but consensus on breakpoints is absent and surveillance is impossible. Antimicrobial stewardship is therefore in jeopardy. This review highlights these difficulties and in particular the efficacy of current non-antibiotic antimicrobials used in dressings, their efficacy, and the challenges of translating in vitro efficacy data to the efficacy of dressings in patients. This review calls for a unified approach to developing standardized methods of evaluating antimicrobial dressings that will provide an improved basis for practitioners to make informed choices in wound care.